Students’ self-consciousness of comic strips as narrative writing teaching aids - Lilies Youlia Friatin; Angelo Osunero (Universitas Sarjanawiyata Tamansiswa, 2022)
The use of comic strips as teaching aids for narrative writing is the subject of this study. This study used comic strips in the context of narrative writing to examine students' feelings of self-consciousness. The researchers conducted a case study to gather qualitative information for this study. A questionnaire was used as a research instrument in this study. The form of the questionnaire used by the researchers is a close-ended question with a short rating questionnaire (strongly agree, agree, neutral, disagree or strongly agree) which consists of ten statements. To analyze the data, the researchers used the formula of the computation for calculating the data to be a percentage of each student's response to each questionnaire item by presenting them on the table and then described it as the questionnaire was examined. The findings indicate that using comic strips as teaching aids for the narrative writing curriculum is well received by students. It showed that the students gave positive responses towards the implementation of comic strips as teaching media in narrative learning material. Almost all of the students in the classroom were interested and enjoyed it while the researchers implemented the comic strips. The students are active in class activities. They felt using the comic strips as a learning media makes them better able to develop their imagination and create ideas for developing the stories discussed because, in the comic, the explanations accompanied by pictures and dialogues make it easier for them to interpret the stories or material discussed, even though in terms of language skills and vocabulary are inadequate.